2022
DOI: 10.1111/aji.13584
|View full text |Cite
|
Sign up to set email alerts
|

Plasma E‐selectin and kallistatin as predictive markers of histologic chorioamnionitis in women with preterm premature rupture of membranes

Abstract: Problem:We aimed to assess the predictive potential of 12 plasma biomarkers to predict acute histologic chorioamnionitis (HCA) in women with preterm premature rupture of membranes (PPROM) and to develop multi-biomarker panels based on these biomarkers in combination with widely used conventional laboratory markers. Method of study:This was a retrospective cohort study involving 81 singleton pregnant women (24-34 weeks of gestation) who delivered within 96 h of blood sampling.White blood cell (WBC) count, diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 78 publications
6
15
0
Order By: Relevance
“…23,[63][64][65][66] In the context of PPROM, shotgun proteomics of pooled AF samples showed that kallistatin expression is significantly downregulated in women with PPROM complicated with both HCA and MIAC compared with those without these conditions 67 Similarly, in a recent study, we showed that kallistatin levels are significantly decreased in the plasma of patients with acute HCA in the context of PPROM. 68 In line with previous studies, 23,[63][64][65]67 we demonstrated herein that decreased plasma kallistatin levels are independently associated with microbial-associated HCA in PTL patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…23,[63][64][65][66] In the context of PPROM, shotgun proteomics of pooled AF samples showed that kallistatin expression is significantly downregulated in women with PPROM complicated with both HCA and MIAC compared with those without these conditions 67 Similarly, in a recent study, we showed that kallistatin levels are significantly decreased in the plasma of patients with acute HCA in the context of PPROM. 68 In line with previous studies, 23,[63][64][65]67 we demonstrated herein that decreased plasma kallistatin levels are independently associated with microbial-associated HCA in PTL patients.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, kallistatin acts as a negative acute‐phase protein, which is rapidly reduced after lipopolysaccharide‐induced inflammation, 62 and thus its levels in plasma tend to decrease in several inflammatory diseases, such as inflammatory bowel disease, septic syndrome, severe pneumonia, and obesity 23,63–66 . In the context of PPROM, shotgun proteomics of pooled AF samples showed that kallistatin expression is significantly downregulated in women with PPROM complicated with both HCA and MIAC compared with those without these conditions 67 Similarly, in a recent study, we showed that kallistatin levels are significantly decreased in the plasma of patients with acute HCA in the context of PPROM 68 . In line with previous studies, 23,63–65,67 we demonstrated herein that decreased plasma kallistatin levels are independently associated with microbial‐associated HCA in PTL patients.…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, it is of particular clinical importance to identify patients with PPROM complicated by microbial‐associated HCA, preferably based on non‐invasive biomarkers, to allow tailoring suitable and timely treatment strategies. In a previous study, we reported that low plasma levels of E‐selectin, and maternal C‐reactive protein levels and white blood cell counts could be used as independent biomarkers for microbial‐associated HCA in pregnancies complicated PPROM 53 . Herein, we further demonstrated that elevated CVF levels of IL‐6, IL‐8, M‐CSF, MMP‐8, and TNFR2 are also independently associated with microbial‐associated HCA.…”
Section: Discussionsupporting
confidence: 53%
“…Further sufficiently powered prospective studies are needed to confirm our observations and to elucidate the possible mechanisms by which HCA and associated infection/inflammation affect the levels of these proteins in the CVF of patients with PPROM. In addition, whether these newly identified CVF‐based biomarkers can contribute for predicting PPROM‐associated acute HCA when used in combination with other currently available tests/biomarkers (e.g., C‐reactive protein, E‐selectin, kallistatin, MMP‐9, IL‐6, IGFBP‐1, and S100 A8/A9 in the blood) should be addressed in future investigations 36,53 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation